A new species of the genus Lathriopyga Caroli, 1912 (Collembola, Neanuridae, Neanurinae) from the Republic of Moldova - Buşmachiu, Galina; Deharveng, Louis; Weiner, Wanda Maria (Zootaxa, 2010)
A new species of the genus Lathriopyga Caroli, from the Republic of Moldova is described and figured. It differs from its closest relative, Lathriopyga bulgarica Smolis, Skarżyński & Pomorski, by the presence of 3+3 chaetae Di on Abd. V, Di1 as a long macrochaeta, Di2, Di3 as short macrochaetae, presence of three chaetae Oc on head and the form of mandible (with 6–7 denticles appearing as a fringe between apical and basal teeth).